Effect of Meat Type, Animal Fatty Acid Composition, and Isothermal Temperature on the Viscoelastic Properties of Meat Batters. Issue 6 (22nd May 2018) - Glorieux, Seline; Steen, Liselot; De Brabanter, Jos; Foubert, Imogen; Fraeye, Ilse
Abstract : Abstract: The aim of this research was to simultaneously study the effect of meat type (chicken breast and leg meat), animal fatty acid composition (selected pork backfats having a low and high degree of saturation, respectively), and isothermal temperature (50, 60, 70, and 80 °C) on the viscoelastic properties of meat batters during and after application of different time–temperature profiles. Gelation of meat proteins contributed most to the viscoelastic properties of meat batters during heating, whereas crystallization of the lipids especially contributed to the viscoelastic properties during the cooling phase. Although the meat type had little effect on the final viscoelastic properties of the meat product, the fatty acid composition had a clear impact on the melting peak area (and therefore solid fat content) of lard, and subsequently on the final viscoelastic properties of meat batters prepared with different types of fats, with higher G ′ (elastic modulus) values for the most saturated animal fat. The crystallization of the fat clearly transcended the effect of the meat type with regard to G ′ at the end of the process. With increasing (isothermal) temperature, G ′ of meat batters increased. Therefore, it could be concluded that the structural properties of heated meat batters mainly depend on the heating temperature and the fatty acid composition, rather than the meat type. Practical Application: Quality characteristics of cooked sausages depend on multiple factors such as the meat and fat type, non‐meat ingredients and processing conditions. From this study it could be concluded that the structural properties of cooked sausage batters mainly depend on the heating temperature and the fatty acid composition, rather than the meat type. Because the fatty acid composition of different animal fats differs widely, these results may be a concern for all manufactures of cooked sausages products with regard to the product structure and final texture, keeping in mind that rendered fat was used in this study, which is not common in sausage making.